Adaptive mechanisms to hypoxia and hyperoxia in juvenile turbot, Scophthalmus maximus - Yi Chen; Yuntian Zhang; Rongwei Zhang; Hongsheng Deng; Xiangyu Meng; Kotoya Inaba; Tatsu Osato; Xiaoran Zhao; Xiaoran Zhao; Yuzhe Han; Yuzhe Han; Tongjun Ren; et al. (Frontiers in Marine Science)
In recirculating aquaculture systems (RAS), the impact of dissolved oxygen (DO) fluctuations on turbot is still not fully understood. This study investigated these impacts by selecting 135 turbot (average dry weight: 6.0 ± 0.5 g) and exposing them to three DO levels: hypoxia (4.0 ± 0.5 mg/L), normoxia (7.5 ± 0.5 mg/L), and hyperoxia (23.5 ± 0.5 mg/L). These groups were labeled as LF (low oxygen), NF (normal oxygen), and HF (high oxygen). The study aimed to explore the adaptive mechanisms of turbot under hypoxic and hyperoxic conditions, using microbiome, transcriptome, and hematological analyses over a 40-day period. The results suggest that hyperoxia significantly enhances turbot growth without compromising the composition of intestinal microbiome, whereas hypoxia markedly impairs growth and induces alterations in intestinal microbiome. Transcriptomic analysis revealed various pathways implicated in adaptation to both hypoxic and hyperoxic conditions, encompassing amino acid metabolism, protein metabolism, lipid metabolism, carbohydrate metabolism, the PPAR signaling pathway, etc. However, pathway changes are not completely consistent. For instance, pancreatic secretion is crucial for hyperoxia adaptation, while the HIF1α pathway plays a key role in hypoxia adaptation and tissue repair. Furthermore, genes ATP6, HIF1, HSP90, and CYP450 exhibited high expression levels during hypoxia, whereas Hbae5 and Man-SL showed elevated expression during hyperoxia. In hematological indicators, there are ways to help adapt to hypoxia and hyperoxia, including increased red blood cell (RBC) and hemoglobin (HGB) counts; gas and ion balance; elevated blood urea nitrogen (BUN) and malondialdehyde (MDA); increased polyphenol oxidase (PPO) and lysozyme (LZM) activity. Although turbot have adaptive mechanisms to both hypoxia and hyperoxia, extended exposure to hypoxia detrimentally affects growth, whereas hyperoxia facilitates it. These findings provide significant insights into the adaptive mechanisms of turbot in response to fluctuating DO levels.